JEJAK KIAI AGENG SINGOPRONO - Wardana, Bintang Kusuma (Program Studi Sejarah Peradaban Islam Fakultas Ushuluddin Adab dan Dakwah IAIN Manado, 2024)
Kiai Ageng Singoprono is one of the important and influential figures in the spread of Islam on the island of Java. History records that Kiai Ageng Singoprono was a cleric who taught Islamic values and science. By tracing its traces, we can understand the social dynamics that occurred and how Islam adapted to developments in the area. This research aims to describe the traces of Kiai Ageng Singoprono in the Islamization of the Simo area, Boyolali. The method used in this research is descriptive qualitative. This research data is in the form of notes from interviews regarding the traces of Kiai Ageng Singoprono in the spread of Islam in Simo, Boyolali. The data source for this research is informants. The data collection technique uses the interview method which is used to collect data from informants in the village. The research results show that Kiai Ageng Singoprono's footsteps in Simo, Boyolali have had a big influence on the people of Simo, Boyolali. His footsteps included the spread of Islam through agricultural, spiritual paths, and applying the nature of generosity.